2000
DOI: 10.1074/jbc.m004035200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Na+/Ca2+ Exchanger Gene Leads to Cardiomyocyte Apoptosis and Defects in Heartbeat

Abstract: Ca2؉ , which enters cardiac myocytes through voltagedependent Ca 2؉ channels during excitation, is extruded from myocytes primarily by the Na ؉ /Ca 2؉ exchanger (NCX1) during relaxation. The increase in intracellular Ca 2؉ concentration in myocytes by digitalis treatment and after ischemia/reperfusion is also thought to result from the reverse mode of the Na ؉ /Ca 2؉ exchange mechanism. However, the precise roles of the NCX1 are still unclear because of the lack of its specific inhibitors. We generated Ncx1-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 30 publications
7
146
0
Order By: Relevance
“…These observations suggest that NCX1 is critical to early cardiac development. Other groups also reported similar cardiac defect induced lethality in the NCX1 KO mice (Wakimoto et al, 2000;Koushik et al, 2001). Recent report showed that transgenic re-expression of a NCX1 isoform was insufficient to rescue a lethal phenotype of NCX1 KO mice (Conway et al, 2002).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…These observations suggest that NCX1 is critical to early cardiac development. Other groups also reported similar cardiac defect induced lethality in the NCX1 KO mice (Wakimoto et al, 2000;Koushik et al, 2001). Recent report showed that transgenic re-expression of a NCX1 isoform was insufficient to rescue a lethal phenotype of NCX1 KO mice (Conway et al, 2002).…”
Section: Introductionmentioning
confidence: 74%
“…The null mutation of the NCX1 gene caused lethality in mice embryos (Cho et al, 2000;Wakimoto et al, 2000;Koushik et al, 2001;Rheuter et al, 2002). Within embryonic day (ED) 9.0-9.5, the heart of the knock-out (KO) mice showed an irregular contraction and a pericardial effusion (Cho et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…During the revision of our manuscript, this result was recently substantiated from two independent studies on NCX-1-deficient mice in which hearts form, but do not beat (Wakimoto et al, 2000;Koushik et al, 2001). In the stage 11-12 chick embryo within 8 hr of KB-R7943 exposure, heart rate is significantly reduced and, by 22 hr, is totally arrested while control hearts are still beating.…”
Section: Kb-r7943 Inhibitionmentioning
confidence: 80%
“…These mice were originally described as having embryonic lethal vascular patterning defects, but a subsequent study demonstrated prolonged embryonic viability with cardiomyocyte-specific restoration of NFAT function (Graef et al, 2001a;Bushdid et al, 2003). The dependence of vascular development on cardiac function also has been demonstrated in mice deficient in Ncadherin or the sodium/calcium exchanger Ncx1 (Wakimoto et al, 2000;Luo et al, 2001). The requirement for cardiac function for vascular plexus remodeling was observed as early as 1918, when W.B.…”
Section: Discussionmentioning
confidence: 99%